Valuation effects of mergers and acquisitions in freight transportation - Andreou, Panayiotis; Panayides, Photis; Louca, Christodoulos (My University, 2012)
This study investigates valuation effects of mergers and acquisitions in the freight transportation industry. It is found that mergers and acquisitions create synergistic gains, especially tender offers, consistent with the view that freight transportation mergers and acquisitions occur for synergistic reasons rather than management's desire for empire building or perk consumption. Both target's and bidder's shareholders are better-off, but most of the synergistic gains accrue to the target's shareholders. Targets' valuation effects are greater for vertical rather than horizontal mergers, indicating a positive valuation for firms that control and manage a more extensive supply chain. The bidders' wealth effects are greater for friendly mergers. Overall, the findings have important implications for professional practice and the development of the theoretical literature
Keywords: Transportation Research; Logistics; Consolidation and merger of corporations; Transportation